Materials selection of a bicycle frame using cost per unit property and digital logic methods - Maleque, Md. Abdul; Sarker, Dyuti (Universiti Malaya, 2010)
The aim of this paper is to develop the material selection method and select the optimum material for the application of folding bicycle frame. Two methods are introduced for the selection of materials, such as cost per unit property and digital logic methods. In cost per unit property, only one property (strength) is considered whereas in digital logic method, multiple properties such as tensile strength, yield strength, young’s modulus, toughness and density were considered for the optimum selection of the materials. The Ashby’s material selection chart was used for the initial screening of the candidate materials. The results are presented both in tabular and graphical forms. The materials selection method showed that AISI 1020 steel, Ti-alloy, carbon fiber reinforced polymer (CFRP), kevlar fiber reinforced polymer (KFRP) and glass fiber reinforced polymer (GFRP) are the candidate materials for the design of bicycle frame. From the cost per unit property method it is found that the KFRP shows the least cost material followed by AISI 1020 steel material. The digital logic method also showed the highest figure of merit value for KFRP material followed by AISI steel and Ti-alloy. Based on the developed materials selection method and analysis of the few candidate materials it can be concluded that the KFRP is the suitable material for the design and application of bicycle frame.